A escola como espaço/tempo de auto(trans)formação permanente e mudança da prática docente - Poglia, Patrícia Dalmaso (2016)
This Master's Thesis Project is part of the Research Line/LP1- Training, Knowledge and Professional Development of the Postgraduate Program in Education of the Federal University of Santa Maria/RS. The objective of this study was to understand what knowledge and learning necessary for permanent self(trans)formation and change of the teacher s practice in order to recognize and assumed the school as space/time for this construction. For this, we listed as specific objectives how is the participation of educators in the continuing education building process carried out at school; perform a critical and reflective reading about the teacher s practice and if the continuing education provides the peer integration; notice from the school context how continuing education can contribute to innovation practices; identify the theoretical frameworks and strategies delimit the school formations and how they relate to the demands of everyday activity and understand from the voices of teachers, if the continuing education can be considered as a permanent self(trans)formation factor, construction and social intervention. We realize that the school is undergoing a serious crisis of identity which runs through on individual, professional and management aspects. The continued training to which teachers are submitted are decontextualized of school reality and away from the desires of the majority of professionals working in it. The main motivation was to provide moments of reflection and self(trans)formation from meetings in Dialogical Circles Investigative-training, these based on Freire's Culture Circles. The theoretical and conceptual contributions were mainly grounded on the propositions of Paulo Freire (1967,1981,1988,1992,1997,1999, 2000, 2011, 2015) in dialogue with other authors such as: NÓVOA (1992, 1995, 2009), GHEDIN and FRANCO (2011), ARROYO (2000), TARDIF (2006, 2010) IMBERNÓN (2009, 2010, 2011, 2012), among others. Methodologically this study was based on a qualitative approach of a case study, supported by YIN (2010), TRIVINÕS (1987), LÜDKE and ANDRÉ (2010) and as research-forming characteristics, as coauthors subjects participate actively of all stages of the research, we mention JOSSO (2010) and HENZ (2010, 2012, 2014, 2015) to give the theoretical support necessary to carry out the research. For the speech of the coauthors subject of the research, we proceed from the perspective of Philosophical Hermeneutics of GADAMER (2007). We wanted with this study, understand that the teacher in their uniqueness and in line with their peers is essential in building new practices, with the school as a place of training, innovation and sharing, being able to effectively contribute to your self(trans)formation and of the education professionals engaged in this task considering the importance of contextualized continuing education, built within the school environment, in order to the school to provide situations of reflection and awareness, seeking to establish an ongoing process of continuing education and collaborative culture to intervene individual and collectively in the social reality of where the school is inserted.